The Effect Of Customer Satisfaction And Trust On Customer Loyalty In The Shopee Marketplace - Nyoman Suardhita; Rini Martiwi; Instianti Elyana; Aan Rahman (Quantitative Economics and Management Studies, 2024)
This research aims to test the influence of trust and customer satisfaction on customer loyalty, test the influence of trust on customer loyalty and test the influence of customer satisfaction on customer loyalty. This research uses a quantitative descriptive method by distributing questionnaires via Google Form with purposive sampling, namely Shopee users as an online shopping platform for consumers in Depok. A purposive sampling method of 150 respondents was used for the sampling. SPSS 26 was used to calculate the multiple linear regression variable test to analyze the research data results. The research results show that customer satisfaction and trust are important in forming customer loyalty to Shopee. Factors such as ease of use, wide product selection, responsive customer service, and security of online transactions influence customer satisfaction levels. In addition, customer trust in the security of online transactions and product quality also plays a key role in building long-term relationships between customers and e-commerce platforms. The R square value of 0.725 indicates that most of the variation in customer loyalty levels can be explained by customer satisfaction and trust in Shopee in Depok. At the same time, the rest is influenced by other factors, such as quality. Product and brand preferences.